Reading Literacy: How is it Implemented at the Elementary School Level? - Akmalia, Putri; Alaziz, Farchan; Zuraida (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to analyze students' reading literacy at elementary school level. This research uses a quantitative approach with a survey research type. The subjects of this research were all high class students of Madrasah Ibtidaiyah Negeri 10 Aceh Besar with a sample of 15 students. The sampling technique used in this research is Cluster Random Sampling. The data in this study was collected using a questionnaire. The data obtained is quantitative data which is then analyzed using Descriptive Statistics techniques. The results of this research show the high reading literacy of students in the high class of Madrasah Ibtidaiyah Negeri 10 Aceh Besar. There were 10 students who achieved the highest reading literacy with a presentation of 0.66%. A total of 2 students achieved good reading literacy with a presentation of 0.13%. 1 student achieved poor reading literacy with a presentation of 0.66%. And what was very bad was that 2 students achieved reading literacy with a presentation of 0.13%. It can be concluded that this research shows the high reading literacy of students in the high class with a very good categorization using a 1234 Likert scale. With a total of 15 students, of which 10 are have excellent reading literacy.